Telitacicept versus belimumab in proliferative lupus nephritis - Wang, Chang; Zhang, Man-Zhu; Yun, Xiao-Ying; Li, Ling-Xu; Shan, Jia-Wei; Liu, Biao; Li, Bing (Frontiers in Immunology, 2026)
Background and objectivesProliferative lupus nephritis (LN) is a severe pathological type of systemic lupus erythematosus with a high risk of progression to chronic kidney disease and end-stage renal disease. The prognosis of patients with proliferative LN has improved with advancements in treatment regimens. However, more effective molecular targeted therapies are still needed. This study aimed to evaluate the efficacy and safety of two novel biologics, telitacicept and belimumab, in the treatment of proliferative LN.MethodsTwenty-eight individuals diagnosed with proliferative LN (class III/IV ± V) were retrospectively enrolled at the Second Affiliated Hospital of Hainan Medical University between January 2021 and May 2025 and received either telitacicept (n=18) or belimumab (n=10) in conjunction with standard therapy for more than 24 weeks. The renal response rates were the evaluated outcome.ResultsA total of 28 patients were enrolled, with 18 receiving telitacicept and 10 receiving belimumab. At 8 weeks, the telitacicept group presented a greater renal remission rate, with 8 patients (44.4%) achieving a complete renal response (CRR), 7 patients (38.9%) achieved partial renal response (PRR), and 3 patients (16.7%) showed no renal response (NRR). In contrast, only 6 patients (60%) achieved PRR in the Belimumab group. The renal remission rate at 8 weeks was significantly higher in the Telitacicept group compared to the Belimumab group (p=0.04). The telitacicept group also demonstrated greater improvements in the SLEDAI-2K score and complement C3 level. At 24 weeks, 72.2% of the telitacicept group achieved a CRR, whereas 60% of the belimumab group achieved a CRR, with no significant difference in renal response rates. Glucocorticoid and immunosuppressant use was successfully reduced in both groups. Additionally, both groups showed improvements in clinical parameters, but no significant difference was noted at 24 weeks.ConclusionsIn this preliminary study, telitacicept appears to induce earlier renal and immunologic remission than belimumab, along with a potential reduction in the need for glucocorticoids and immunosuppressants. Further validation in larger studies is needed.